TINGKAT UMUR DAN PARITAS IBU HAMIL TRIMESTER III DENGAN KUNJUNGAN K4 - Henny Juaria (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2019)
Introduction: K4 is contact with pregnant women with health workers 4 or more, to get antenatal care according to established standards. The national and provincial target of East Java for K4 visits is 95%. East Java Health Office data for K4 achievement in 2017 amounted to 79.98%. In Puskesmas Manukan Kulon Surabaya K4 visits from 2015 amounted to 60.73%, 2016 amounted to 72.16% and in 2017 amounted to 87.97% are still below the national target of 95% in 2017. Based on this problem it is deemed necessary to conduct a study aimed at to find out is there a relationship between age and parity of TM III pregnant women with K4 visit at Manukan Public Health Center in 2018. Method: This study was an analytic study with cross sectional design. Sampling by probability sampling with systematic random sampling techniques a sample of 181 people. Intake of a cohort of pregnant women. The results of the study were made frequency tabulation, cross tabulation and analyzed by Chi-Square Test with the provisions ?2. 3.84 (? = 0.05%). Results: From the results of the study showed that many K4 visits were at the age level of 20-35 as many as 40 people (63.49%) and in mothers with primiparous parity as many as 51 people (62.20%). Based on the Chi-Square test on the age and parity level obtained itung2calculate> T2Table so H0 is rejected. Discussion: There is a relationship between age level and parity of third trimester pregnant women with K4 visit. Where health workers are expected to be active in providing motivation and counseling during pregnancy to pregnant women to check their pregnancy regularly at least 4 times during pregnancy. Thus complications in pregnancy can be detected early and K4 visits can be achieved.